Formal Ontologies Meet Industry 7th International Workshop, FOMI 2015, Berlin, Germany, August 5, 2015, Proceedings - Cuel, Roberta; Young, Robert (Lecture Notes in Business Information Processing, 2015)
This book constitutes the proceedings of the 7th International Formal Ontologies Meet Industries Workshop held in Berlin, Germany, in August 2015. The 11 full research papers accepted for FOMI 2015 were selected from 18 submissions. The papers focus on theoretical studies of formal ontologies committed to provide a sound basis for industrial applications and to allow formal representation of corporate knowledge, and on business experiences in case studies that single out concrete problems and possible solutions in the creation and deployment of formal ontologies. Overall, they provide valuable insights into the current state of progress in supporting industrial information and knowledge sharing through the development of formal ontologies.